The impact of sleep amount and sleep quality on glycemic control in type 2 diabetes: A systematic review and meta-analysis. (February 2017) - Lee, Shaun Wen Huey; Ng, Khuen Yen; Chin, Weng Khong
Summary: Recent epidemiological studies have suggested that there is an association between glycemic control and sleep disturbances in patients with type 2 diabetes, but the extent is unclear. A systematic literature search was performed in nine electronic databases from inception until August 2015 without any language restriction. The search identified 20 studies (eight studies reporting duration of sleep and 15 studies evaluating sleep quality), and 15 were included in the meta-analysis. Short and long sleep durations were associated with an increased hemoglobin A1c (HbA1c) (weighted mean difference (WMD): 0.23% [0.10–0.36], short sleep; WMD: 0.13% [0.02–0.25], long sleep) compared to normal sleep, suggesting a U-shaped dose–response relationship. Similarly, poor sleep quality was associated with an increased HbA1c (WMD: 0.35% [0.12–0.58]). Results of this study suggest that amount of sleep as well as quality of sleep is important in the metabolic function of type 2 diabetes patients. Further studies are needed to identify for the potential causal role between sleep and altered glucose metabolism.